Pengelolaan Keuangan Untuk Usaha Kerajinan Tangan Kain Perca Dalam Rangka Meningkatkan Produktivitas Masyarakat - Nur’aini, Annisa; Karunia Wati, Niken; Shavira Darman, Nur; Rahayu, Tika (Rifa'Institute, 2022)
Finances need to be managed properly, when management is done carelessly, it can be bad. The bad effect is in the form of unsuccessful business development, problems related to money can only be solved with money, with good management, business finances can be allocated to solve problems that exist in a business. This Community Service aims to provide knowledge about financial management to start a handicraft business made from patchwork Ex. South Tangerang City. Issues raised regarding how to manage finances effectively. The method used in the implementation of this service is carried out in several preparations, namely (1) Planning (2) Making a financial record book (3) Managing profits to develop the business. The results of this activity are very useful for business people Ex. Buaran in improving the way of effective financial management in the business being run.